Encountering Octavius: Reading Minucius Felix within the Stage Model of Conversion - Dutmer, Evan (Journal of religious and theological information, 2025)
Minucius Felix’s Octavius (ca. 200 CE) is a remarkable document in the history of pagan-Christian interaction in Late Antiquity. The nature of the philosophical exchange between the principal interlocutors makes the Octavius ripe for analysis with tools from contemporary conversion studies. In particular, here I argue that the Octavius—especially in its depiction of the encounter between Octavius, advocate for Christianity, and Caecilius, Roman pagan, a candidate for conversion—aligns remarkably well with Lewis Rambo’s influential Stage Model for Conversion. The text and order of the Octavius will be interpreted according to Rambo’s model for encounter between advocate and prospective convert. The implication of this alignment will be evidence that the Octavius represents a good faith exchange between pagan and Christian in the third century CE. This essay will, further, serve librarians and information professionals in providing resources for patrons interested in Roman Christian-pagan interaction and Early Christianity. The Octavius is unique in offering one of the very few direct Christian-pagan exchanges in Latin. This essay also directs to further reading in Late Antiquity, Early Christianity, Ancient Philosophy, and Conversion Studies.